EUFEMISME DALAM BERITA ELEKTRONIK TRIBUNJABAR.ID EDISI BULAN MEI 2021 - Winata, Nana Triana; Agus Nasihin (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2023)
The purpose of this study was to identify the form of euphemism, the function of euphemism, and the meaning of euphemism. The method used is descriptive qualitative research. The data in this study are in the form of words, phrases, sentences, or euphemistic expressions contained in the May 2021 edition of the electronic news Tribunjabar.id. In this study, there are 49 euphemistic data from the May 2021 edition of Tribunjabar.id as data from May 1 to May 31, 2021. In this study there are 3 data collection techniques, namely reading carefully and thoroughly every word, phrase, sentence, or expression of euphemism contained in the May 2021 edition of the Tribunjabar.id electronic news. The results of this study prove that there is the use of euphemisms in the Tribunjabar electronic news. en May 2021 issue, such as the use of words, phrases, meanings, and functions of euphemisms. (1) The euphemism of the use of words has 5 forms of data in the form of words and the euphemism of the use of words with affixes has 4 forms of data. (2) The euphemism of the use of the phrase has 4 forms. (3) The euphemism of the use of abbreviations in this section is clear and abbreviations are divided into two parts, namely initials and acronyms. The euphemism for the use of abbreviations contains 12 data, including 5 data in the form of initials. There are 7 data forms of acromine expression. (4) The euphemism of the use of loanwords contains 10 forms of data. (5) Euphemisms for the use of foreign terms in 6 forms of data. (6) Euphemisms using metaphors in 4 forms of data. (7) The euphemism of the use of 4 forms of data.